The first finding of Dinophilus gyrociliatus O. Schmidt, 1857 (Annelida, Polychaeta, Dinophilidae) at the Black Sea coast of Crimea - Lisitskaya, E. V.; Boltachova, N. A. (Marine Biological Journal, 2016)
The first finding of the polychaete Dinophilus gyrociliatus O. Schmidt, 1857 on the coast of Crimea is reported. The species occurred in 2015 in the waters of Sevastopol (Kruglaya Bay) at the depth of 3–5 m. This species is characterized by the absence of pigmentation, by the presence of one ciliary ring per body segment and by extreme sexual dimorphism. Reproduction of D. gyrociliatus were investigated in the laboratory. Females released cocoons containing from 3 to 10 eggs. Eggs development took 5 days at 18.0–19.5 ℃. The larvae of two types hatch from the cocoons: large females with a length of 500–600 μm and a width of 150–175 μm and small, rudimentarymales resembling trochophore with a diameter of about 100 μm.